Characteristics and evolution of ground substrate in the black soil area of the residual veins of Changbai mountain - Chen, Zhansheng; Chen, Xue; Tang, Yulei; Huo, Dong; Ai, Xiaojun; Geng, Guoshuai (Frontiers in Earth Science, 2025)
BackgroundThe study of the formation and evolution of black soils holds significant implications for the sustainable utilization of black soil resources and human societal development. However, research exploring the regularity of black soil formation and evolution through surface substrate investigations remains limited.MethodThis paper, based on the novel concept of “surface substrate layer” proposed by China’s Ministry of Natural Resources, takes the black soils in Fengcheng City and Kuandian County of Dandong City, Liaoning Province, China as the research object.ObjectiveThrough integrated analysis of surface substrate classification and geochemical element characterization, this study systematically elucidates the multidimensional controlling mechanisms of parent rock properties on black soil pedogenesis for the first time.ResultsThe results demonstrate pronounced differences in soil characteristics developed from various parent materials. In terms of physical properties: soils formed by the weathering of sedimentary rocks (e.g., carbonate rocks) exhibit finer particle sizes, while soils derived from older metamorphic rocks (e.g., TTG gneiss) have the coarsest particle sizes; soil pH is primarily influenced by parent rock mineral composition, with basic rocks (e.g., basalt) developing acidic soils whereas marble forms neutral soils; soil bulk density correlates with the compactness of parent rocks, with soils developed from Cenozoic basalt exhibiting the highest bulk density. Regarding geochemical characteristics: principal component analysis clearly distinguishes soils developed from different parent rock types, demonstrating their elemental composition inheritance from parent rocks. Chemical index of alteration (CIA) and silica-alumina ratio (Sa) analyses reveal that basic rocks (e.g., Cenozoic basalt) undergo the highest degree of weathering, while metamorphic rocks such as TTG gneiss exhibit the greatest weathering resistance. Beneficial trace elements (e.g., Se, N, P) are generally enriched, but their enrichment levels are closely related to parent rock types. Therefore, lithology of parent rocks serves as the key factor controlling the formation and differentiation of surface substrate properties in the study area’s black soil.ConclusionsThis understanding holds significant scientific importance for deepening the comprehension of black soil formation and evolution patterns, as well as for implementing precise conservation measures and soil quality improvement based on surface substrate investigation backgrounds.